Are people interested in receiving advice from their general practitioner on how to protect their health during heatwaves?: a survey of the German population - Kastaun, Sabrina; Herrmann, Alina; Müller, Beate S.; Klosterhalfen, Stephanie Katharina; Hoffmann, Barbara; Wilm, Stefan; Kotz, Daniel (BMJ open, 2023)
Objective Climate change increases the frequency, intensity and length of heatwaves, which puts a particular strain on the health of vulnerable population groups. General practitioners (GPs) could reach these people and provide advice on protective health behaviour against heat. Data is lacking on whether and what topic of GP advice people are interested in, and whether specific person characteristics are associated with such interests. - Design Cross-sectional, nationwide, face-to-face household survey, conducted during winter 2022/2023. - Setting Germany. - Participants Population-based sample of 4212 respondents (aged 14-96 years), selected by using multistratified random sampling (50%) combined with multiquota sampling (50%). - Main outcome measure Interest in receiving GP advice on health protection during heatwaves (yes/no), and the topic people find most important (advice on drinking behaviour, nutrition, cooling, cooling rooms, physical activity or medication management). Associations between predefined person characteristics and the likelihood of interest were estimated using adjusted logistic regressions. - Results A total of 4020 respondents had GP contact and provided data on the outcome measure. Of these, 23% (95% CI=22% to 25%) expressed interest in GP advice. The likelihood of expressing interest was positively associated with being female, older age (particularly those aged 75+ years: 38% were interested), having a lower level of educational attainment, having a migration background, living in a more urban area, and living in a single-person household. It was negatively associated with increasing income. Advice on medication management received highest interest (25%). - Conclusions During winter season 2022/2023, around one quarter of the German population with GP contact—and around 40% of those aged 75+ years—was estimated to have a stated interest in receiving GP advice on protective health behaviour during heatwaves, especially on medication management. Climate change is creating new demands for healthcare provision in general practice. This study provides initial relevant information for research and practice aiming to address these demands.